Understanding the influence of user participation and involvement on system success: a systematic mapping study - Abelein, Ulrike; Paech, Barbara (Software Engineering 2016, 2016)
User participation and involvement in software development are considered to be essential for a successful software system. We think it is important to analyze user participation and involvement in software engineering comprehensively to encourage further research in this area. Objectives: We investigate the evidence on effects of user participation and involvement on system success and we explore which methods are available in literature. Methods: A systematic mapping study was conducted. The systematic search yielded 3,698 hits, from which we identified 289 unique papers. Results: Based on the empirical evidence of the surveys and meta-studies, we developed a meta-analysis of structural equation models. The analysis of the proposed solutions from the method papers revealed a wide variety of user participation and involvement.
Gesehen am 10.06.2020